Entity Type Enhanced Neural Model for Distantly Supervised Relation Extraction (Student Abstract) - Bai, Long; Jin, Xiaolong; Zhuang, Chuanzhi; Cheng, Xueqi (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
Distantly Supervised Relation Extraction (DSRE) has been widely studied, since it can automatically extract relations from very large corpora. However, existing DSRE methods only use little semantic information about entities, such as the information of entity type. Thus, in this paper, we propose a method for integrating entity type information into a neural network based DSRE model. It also adopts two attention mechanisms, namely, sentence attention and type attention. The former selects the representative sentences for a sentence bag, while the latter selects appropriate type information for entities. Experimental comparison with existing methods on a benchmark dataset demonstrates its merits.